1999
DOI: 10.1094/pdis.1999.83.10.913
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Sensitivity in Monilinia fructicola to Propiconazole Following Prolonged Exposure in Peach Orchards

Abstract: The baseline sensitivity of Monilinia fructicola in a peach orchard not previously exposed to demethylation-inhibiting (DMI) fungicides was determined for propiconazole, using the concentration in an agar medium required to suppress radial growth of mycelium by 50% (EC50) The baseline sensitivity was found to be approximately 0.03 μg/ml. Prolonged, regular exposure of the natural population of M. fructicola to propiconazole in the test orchard over a 3-year period (29 total applications) resulted in a wider ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 6 publications
3
34
0
1
Order By: Relevance
“…[19][20][21][22][23] The EC 50 values of this fungicide, established by Stevi c et al [24] for Serbian Venturia inaequalis isolates, were between 0.016 and 0.362 mg L ¡1 . Their study showed that nine V. inaequalis isolates were moderately resistant (RF D 5.1-16.1), and one isolate was resistant to difenoconazole with RF of 22.6.…”
Section: Discussionmentioning
confidence: 98%
“…[19][20][21][22][23] The EC 50 values of this fungicide, established by Stevi c et al [24] for Serbian Venturia inaequalis isolates, were between 0.016 and 0.362 mg L ¡1 . Their study showed that nine V. inaequalis isolates were moderately resistant (RF D 5.1-16.1), and one isolate was resistant to difenoconazole with RF of 22.6.…”
Section: Discussionmentioning
confidence: 98%
“…However, to establish a discriminatory dose that differentiates between baseline (i.e., never exposed to propiconazole) and resistant isolates associated with a control failure, a more comprehensive analysis of field isolates will be needed. For example, a discriminatory dose of 0.3 |ig/ml was established to monitor resistance to propiconazole of M. fructicola, which was 10-fold greater than that of the baseline population (10,42). This is the first report of reduced sensitivity to propiconazole in G. candidum in natural populations occurring in a postharvest setting.…”
Section: Discussionmentioning
confidence: 99%
“…Propiconazole in a different formulation (Tilt; Syngenta Crop Protection) has been and continues to be used as a preharvest treatment to control brown rot caused by M. fructicola. Resistance to propiconazole in M. fructicola has been reported in the southeastern United States (10,31,42) but there are no reports of crop loss or reduced sensitivity of pathogen populations to pre-or postharvest use of propiconazole in California.…”
mentioning
confidence: 99%
“…Indeed, resistance to DMIs has been reported in many different phytopathogenic fungi including Monilinia fructicola, Venturia inaequalis, Podosphaera xanthii, Uncinula necator, Sclerotinia homoeocarpa, Cercospora beticola, etc. [30][31][32][33][34][35] All D. applanata isolates from Serbia were sensitive to tebuconazole with RFs less than 1.9. Even though resistant isolates were not detected in the present study, reported cases of DMI resistance development in the aforementioned plant pathogens imply necessity of establishment of a regular monitoring program for early detection of resistant strains in pathogen's population.…”
mentioning
confidence: 99%